Preparation Of Antithrombin, High Activity Heparin And A Heparin-Antithrombin Complex By A Rapid Two-Step Affinity Method - Jordan, R; Zuffi, T; Fournel, M; Schroeder, D (Thrombosis and Haemostasis, 1981)
The tight binding affinity of antithrombin for heparin makes possible a relatively selective purification scheme based on salt elution from heparin-Sepharose. We have found, however, that purity can often be greatly increased if the elution is carried out with soluble heparin instead. This heparin can be removed from the antithrombin, either in whole or part, by a second affinity step on Concanavalin A Sepharose. The antithrombin, which binds to the matrix through its glycosidic moieties, retains its ability to bind heparin at physiological ionic strengths. Thus, the complex of antithrombin and heparin is readily isolated free of unbound heparin species. The complex can be eluted intact with low ionic strength buffers containing sugars which compete for binding to the lectin. Alternatively, the high activity heparin (400–500 units/mg) can be obtained separately by a 1 M NaCl wash which is then followed by a carbohydrate wash to obtain the purified antithrombin.We have made certain preliminary biochemical and anticoagulant characterizations of these materials. Not unexpectedly, both the high activity heparin and its complex with antithrombin show significantly greater in vitro potency in comparison to unfractionated heparin. In vivo anticoagulant efficacy, as evaluated in a rabbit infusion model, confirmed the in vitro findings and further suggests some potential therapeutic benefit may be derived from infusion of a preformed heparin-antithrombin complex.